Developing Civil Society in the Non-state Sphere: Welfare and Rights-based Organisations Associated with Ethnic Armed Groups in Myanmar. (4th March 2018) - Jagger, Stan
Abstract: Armed groups are usually seen as threats to humanitarian action but less attention has been paid where they provide assistance to constituent populations. Ethnic armed groups (EAGs) in Myanmar have developed associated welfare organisations that perform this role. This article argues this is due to EAG social embeddedness and flexibility to changes in sources of funding and support, and the influence of their relations with international humanitarian organisations. This article further contends a subset of advocacy, health and education organisations have evolved to form a nascent civil society within the political and social non-state sphere of some established EAGs.